The Electrogenic Na+/K+ Pump Is a Key Determinant of Repolarization Abnormality Susceptibility in Human Ventricular Cardiomyocytes: A Population-Based Simulation Study - Britton, Oliver J.; Bueno-Orovio, Alfonso; Virág, László; Varró, András; Rodriguez, Blanca (Frontiers in Physiology, 2017)
Background: Cellular repolarization abnormalities occur unpredictably due to disease and drug effects, and can occur even in cardiomyocytes that exhibit normal action potentials (AP) under control conditions. Variability in ion channel densities may explain differences in this susceptibility to repolarization abnormalities. Here, we quantify the importance of key ionic mechanisms determining repolarization abnormalities following ionic block in human cardiomyocytes yielding normal APs under control conditions. Methods and Results: Sixty two AP recordings from non-diseased human heart preparations were used to construct a population of human ventricular models with normal APs and a wide range of ion channel densities. Multichannel ionic block was applied to investigate susceptibility to repolarization abnormalities. IKr block was necessary for the development of repolarization abnormalities. Models that developed repolarization abnormalities over the widest range of blocks possessed low Na+/K+ pump conductance below 50% of baseline, and ICaL conductance above 70% of baseline. Furthermore, INaK made the second largest contribution to repolarizing current in control simulations and the largest contribution under 75% IKr block. Reversing intracellular Na+ overload caused by reduced INaK was not sufficient to prevent abnormalities in models with low Na+/K+ pump conductance, while returning Na+/K+ pump conductance to normal substantially reduced abnormality occurrence, indicating INaK is an important repolarization current. Conclusions: INaK is an important determinant of repolarization abnormality susceptibility in human ventricular cardiomyocytes, through its contribution to repolarization current rather than homeostasis. While we found IKr block to be necessary for repolarization abnormalities to occur, INaK decrease, as in disease, may amplify the pro-arrhythmic risk of drug-induced IKr block in humans.